Microbiological spectrum of organisms in patients undergoing external ventricular drain insertion at a tertiary care hospital - Mahrukh Afreen; Syed Vaqar Hussain; Aleezay Irfan; Talha Rasool; Muhammad Nadeem; Sumbal Nawaz (Journal of the Pakistan Medical Association)
Objective: To assess the incidence, causative pathogens, and impact of external ventricular drain-related infection on disease prognosis.